2012
DOI: 10.1371/journal.pone.0033850
|View full text |Cite
|
Sign up to set email alerts
|

Sex Matters during Adolescence: Testosterone-Related Cortical Thickness Maturation Differs between Boys and Girls

Abstract: Age-related changes in cortical thickness have been observed during adolescence, including thinning in frontal and parietal cortices, and thickening in the lateral temporal lobes. Studies have shown sex differences in hormone-related brain maturation when boys and girls are age-matched, however, because girls mature 1–2 years earlier than boys, these sex differences could be confounded by pubertal maturation. To address puberty effects directly, this study assessed sex differences in testosterone-related corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 69 publications
(102 reference statements)
8
135
2
4
Order By: Relevance
“…Other developmental studies have also found negative relationships between testosterone and neural characteristics, but most of these have investigated brain structure, not function (Bramen et al, 2012; Bramen et al, 2011; Herting et al, 2012; Neufang et al, 2009; Nguyen et al, 2013). In rats, androgen receptors are weakly to moderately expressed in the forebrain and basal ganglia (Simerly, Chang, Muramatsu, & Swanson, 1990), which could explain relationships between hormone levels and brain response in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other developmental studies have also found negative relationships between testosterone and neural characteristics, but most of these have investigated brain structure, not function (Bramen et al, 2012; Bramen et al, 2011; Herting et al, 2012; Neufang et al, 2009; Nguyen et al, 2013). In rats, androgen receptors are weakly to moderately expressed in the forebrain and basal ganglia (Simerly, Chang, Muramatsu, & Swanson, 1990), which could explain relationships between hormone levels and brain response in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies suggest that underlying hormonal changes may, in part, explain why pubertal status accounts for some of the variance in brain development. Structural MRI (Bramen et al, 2012; Bramen et al, 2011; Herting et al, 2014; Peper et al, 2009), diffusion tensor imaging (Herting, Maxwell, Irvine, & Nagel, 2012), and fMRI (Goddings et al, 2012; Klapwijk et al, 2013; Op de Macks et al, 2011) studies have found relationships between sex steroids and brain anatomy and activity, respectively, in healthy adolescent samples. Pubertal maturation may be particularly relevant to the development of brain systems underlying social and reward-related processing during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bramen et al. (2012) found high testosterone levels to be associated with thinner GM in girls and with thicker GM in boys. In line with these results, untreated MtFs seem to resemble adolescent girls, having similar testosterone levels to adult men, but lower connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…There are clear differences in brain maturation timing among sexes during adolescence (sexual dimorphism). It has been speculated the possible influence of sex hormones on brain maturation (31) leading to the known 1-2 years earlier maturation of the cortex in girls than in boys (32). Not only the developmental speed, but also the volumes differ among sexes, with a greater increase of WM and a greater decrease of GM in boys than in girls, as shown by magnetic resonance imaging studies and specific gender development of certain brain areas during puberty, with increases in left amygdala volume during puberty in males and increases in left striatal and bilateral hippocampal GM volume in females (23,33).…”
Section: Role Of Sex Hormones On Brain Development During Pubertymentioning
confidence: 99%